Anti-Angiogenic Activity of Sabungai (Gynura procumbens) using a Cancer-induced Chicken Embryo - Armie Joyce P. Aterrado (Journal of Healthcare and Biomedical Science, 2024)
Cancer has been increasing over recent years and is considered the primary cause of mortality following cardiovascular disease. Angiogenesis, the biological process by which new blood vessels are generated, plays a crucial role in the growth and spread of tumors. The objective of this study was to assess the anti-angiogenic activity of different Sabungai (Gynura procumbens) leaf extract concentrations in the Chorioallantoic Membrane (CAM) of cancer-induced chicken embryos. The results of a one-way analysis of variance (25.20 ± 2.70, 27.20 ± 1.08, and 22.80 ± 1.66) indicated a statistically significant difference in CAM vascularization between the various treatments. Post hoc analysis utilizing Tukey's Honest Significant Difference (HSD) test revealed that Treatment 2 (300ppt) significantly affected CAM vascularization, as evidenced by an average vascularization count of 27.20 ± 1.08, followed by Treatment 1 (100ppt) and Treatment 3 (500ppt). The results indicated that the extract from Sabungai leaves effectively hinders the formation of new blood vessels in a dose-dependent manner. The highest concentration of leaf extract (500 ppt) resulted in an average vascularization of 22.80 ± 1.66. However, excessively high doses can cause bleeding and embryo death. The results demonstrated that sabungai leaf extract affected blood vessel development in chicken embryos. The results of this research have various implications that contribute to scientific knowledge and potential applications in cancer treatment.